Philanthropy in Practice: Role of Zakat in the Realization of Justice and Economic Growth - Bilal Ahmad Malik (International Journal of Zakat, 2016)
The entire economic scheme developed under the guiding principles of Shari’ah (Islamic Law) envisages an internally balanced system of economy that neither accepts capitalism nor communism in totality. According to the laws, the realization of justice (a’dl) and wellbeing (falah), i.e., the means to seek blessings of God (fadhl al-Allah), determines its principal objectives (maqasid). Nevertheless, the economic structures adopted by the contemporary Muslim societies, in general, are incoherent with the economic philosophy of Islam. They are practically disconnected from the mechanics and efficiency of Islam’s equity instruments and philanthropic institutions. Consequently, as per Marx’s class conflict theory, economic inequality has spread its roots and traumatized the dynamics of participatory economics, distributive justice, and social equality. Factors such as non-inclusive economics, exploitation as a market principle, and concentration of wealth in few pockets have completely transformed Muslim economies into “capitalist” ones. After conducting critical researches vis-à-vis this paradigm shift in the Muslim world, highbrow Muslim intellectuals have reached to this point that alongside with interest-based means of financial intermediation, non-functionality of philanthropic institutions such zakat and baitulmal has practically divided the society into privileged and deprived classes. The economic advantage of “privileged class” over “deprived class” has become one of the major stumbling blocks in the way of achieving welfare and social justice. Under such vulnerable conditions, it is being argued that “reinstitutionalization” of zakat, both at civil society and state level, is the means to provide socio-economic insurance to those who are otherwise neglected. By facilitating the “constructive channelization” of wealth from “privileged class” to “deprived class”, institution of zakat has the potentiality to overcome the problems like relative deprivation, poverty, illiteracy, unemployment, and so on. In this context, giving of zakat must not be seen merely as a religious obligation; on the contrary, it must be examined in relation to its socio-economic effects. The present research is an attempt to answer the question regarding how reinstitutionalization of zakat can help in the minimization of poverty rate and promotion of socio-economic justice in contemporary “unbalanced” Muslim societies. Keywords: Islamic Economics, Zakat, Social Justice, Poverty, Economic Growth